Conference report – 3rd International Interdisciplinary Conference on Health in the Holistic Model International Scientific and Training Conference and International Conference Aesthetics of the Face in a Holistic Approach (Journal of Face Aesthetics, 2024)
On 27.09.2024, the 3rd International Interdisciplinary Conference on Health in the Holistic Model, the International Scientific and Training Conference ‘Facial Aesthetics in the Holistic Approach’ was held at the Congress and Didactic Centre of the Poznan University of Medical Sciences. The conference was organised by the Chair and Department of Oral Surgery, Periodontal and Mucosal Diseases, the Department of Orthodontics and Masticatory Dysfunction, the Department of Clinical Psychology, the Department of Social Sciences and Humanities, in cooperation with the Polish Society for Facial Aesthetics. A distinguished group of theoreticians and practitioners representing Dutch and Polish research centres took part.
Keywords: international conference; facial aesthetics; facial aesthetics from a holistic perspective; minimally invasive procedures